Teaching Engineering and Food: From Traditional Approaches to a Flipped Course on Gastronomic Engineering - Aguilera, José M. (Food Eng Rev, 2021)
Understanding concepts of food engineering (FE) is fundamental for professionals in the discipline, necessary for food scientists, appealing to non-food science students, and valuable for curious cooks. The challenge of teaching FE is delivering meaningful learning outcomes to the different backgrounds, motivations, and interests of the audiences. This article delves into the origins of FE in academia and the influence on teaching of an expanding food processing industry. Current trends demand a FE education with a wider scope, focused on consumer needs and wants that convey elements of food product design, sustainability, innovation, and culinary applications, among others. Although the core concepts of FE have remained practically the same, new teaching methodologies call for expanded computational abilities, ample access to online contents, and active learning, student-centered approaches. As a case study, we describe the implementation of an elective flipped classroom course on engineering, science, and gastronomy for undergraduate students that include in-class demonstrations by chefs.